A critical analysis of universal literature on graduate employability (Journal for Studies in Humanities and Social Sciences, 2019)
Enhancing graduate employability is fundamental to higher education institutions’ role of producing human capital that is capable of performing competitively in the contemporary labour market. This pa-per presents a synoptic review of literature on graduate employability with particular focus on the conceptual and theoretical background as well as models and approaches for enhancing employability at-tributes. The analysis established that the discourse of graduate employability is central to higher education provision across the globe. The notion of graduate employability has evolved from conceptualiza-tion to the development of instruments for guiding integration of graduate employability attributes in higher education curricula. The paper provides a synthesis of existing research and makes recommendation for further research on strengthening collaboration between higher education institutions and the industry to enhance graduate employability.